2022
DOI: 10.3390/ijms23136996
|View full text |Cite
|
Sign up to set email alerts
|

Fibrogenic Pathways in Metabolic Dysfunction Associated Fatty Liver Disease (MAFLD)

Abstract: The prevalence of nonalcoholic fatty liver disease (NAFLD), recently also re-defined as metabolic dysfunction associated fatty liver disease (MAFLD), is rapidly increasing, affecting ~25% of the world population. MALFD/NAFLD represents a spectrum of liver pathologies including the more benign hepatic steatosis and the more advanced non-alcoholic steatohepatitis (NASH). NASH is associated with enhanced risk for liver fibrosis and progression to cirrhosis and hepatocellular carcinoma. Hepatic stellate cells (HSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 142 publications
0
17
0
Order By: Relevance
“…Liver is the core organ that regulates glucose and lipid metabolism. Nonalcoholic fatty liver disease (NAFLD) is one of the most common liver diseases and encompasses a wide range of downstream pathologies, including simple steatosis, steatohepatitis, advanced fibrosis, and cirrhosis [ 43 , 44 , 45 ]. After consumption of a high carbohydrate diet, patients with insulin resistance present lower glucose uptake and glycogen synthesis in skeletal muscle, leading to a doubling of both liver triglyceride levels and hepatic de novo lipogenesis [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liver is the core organ that regulates glucose and lipid metabolism. Nonalcoholic fatty liver disease (NAFLD) is one of the most common liver diseases and encompasses a wide range of downstream pathologies, including simple steatosis, steatohepatitis, advanced fibrosis, and cirrhosis [ 43 , 44 , 45 ]. After consumption of a high carbohydrate diet, patients with insulin resistance present lower glucose uptake and glycogen synthesis in skeletal muscle, leading to a doubling of both liver triglyceride levels and hepatic de novo lipogenesis [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“… 78 Several toxic lipids, such as fatty acids, cholesterol, oxidized low-density lipoproteins, and others, promote macrophage activation, upregulate their proinflammatory phenotype, induce hepatic stellate cell activation (either directly or indirectly via increased inflammation, Figure 1 ), and promote NASH pathogenesis. 79 , 80 , 81 , 82 Free cholesterol is a key lipotoxic molecule in the context of NASH. 81 , 83 In animal models of NAFLD, several studies have demonstrated the importance of dietary cholesterol in promoting inflammation, fibrosis, and NASH pathogenesis.…”
Section: Role Of Hepatic Stellate Cells In Nonalcoholic Fatty Liver D...mentioning
confidence: 99%
“…Specifically, myeloid cell-specific IRF5-deficient mice are protected from metabolic stress-induced liver fibrosis and exhibit an immunosuppressive and anti-apoptotic transcriptional programme (Alzaid et al, 2016). Furthermore, macrophage derived galectin-3 promotes HSC activation (Subramanian et al, 2022). Galectin-3 is required for TGFβ-dependent HSC activation; in a toxin-induced Under homeostatic conditions, the liver resident KCs exhibit self-renewal capacity, are located in close proximity to the LSECs, express the markers CLEC4F, TIM4 and CLEC2 and exert homeostatic actions.…”
Section: Efferocytosis and Hepatic Macrophage Activationmentioning
confidence: 99%
“…Hepatocyte death, a process fostering macrophage recruitment and activation, also drives HSC activation and fibrosis development during NASH (Subramanian et al., 2022). Following hepatocyte death, macrophages clear the apoptotic cells via efferocytosis, which initiates resolution of inflammation pathways (Kourtzelis et al., 2020).…”
Section: Introductionmentioning
confidence: 99%